Back to Basics: CLABSI Reduction Through Implementation of an Oral Care and Hygiene Bundle. (September 2019) - Kemp, Gina; Hallbourg, Melissa; Altounji, Diane; Secola, Rita
Children with cancer often undergo treatments that render them severely immunocompromised. Side effects of treatment place them at risk for developing oral mucositis (OM), which can potentially lead to infection and bacteremia. Staff nurses on an inpatient pediatric oncology unit noted inconsistent daily oral hygiene practices despite assessing OM consistently. Basic oral hygiene can reduce the severity of OM, and evidence-based bundled care has shown to increase consistency of practice. Based on findings and recommendations from the literature, an oral care and hygiene bundle was developed. The oral care bundle included a soft bristled toothbrush, fluoride toothpaste, twice-daily brushing and sodium bicarbonate rinses, lip balm, and oral moisturizer. The hygiene component consisted of a daily bath or shower and daily linen changes. Education on the rationale and purpose for the use of an oral care and hygiene bundle was provided to the inpatient direct care staff prior to implementation on two inpatient oncology units. Audits were performed to measure the adherence of the oral care and hygiene bundle. Central line–associated bloodstream infections were measured in collaboration with the quality and infection prevention departments. Since the oral care and hygiene bundle was implemented, laboratory-confirmed bloodstream infection rates decreased from 1.05 to 0.54 per 1, 000 catheter days, while mucosal barrier injury rates decreased from 2.98 to 1.27 per 1, 000 catheter days.